Chaos - Johansen, Iris (New York : Grand Central Publishing, 2020)
"Iris Johansen introduces a new kickass female protagonist, Alisa Flynn, a CIA agent who may be willing to go rogue if it means catching the most heartless band of criminals she's ever encountered. Alisa is aided by mysterious billionaire-genius-inventor Gabe Korgan and recurring character Margaret Douglas, an animal whisperer who brings along her beloved dog Juno to fight alongside them. Alisa is determined to rescue schoolgirls kidnapped from their African boarding school, in a ripped-from-the-headlines story. But Alisa is hiding her personal stake in the rescue from Korgan, and when the truth gets out, the stakes grow even higher. Now Alisa and Gabe's budding relationship may be at a breaking point"--
Kirkus Reviews
Booklist
Publishers Weekly
Library Journal Prepub Alert
Adult
Keywords: United States -- Central Intelligence Agency -- Fiction; Missing persons -- Fiction; Mystery fiction; Police -- Fiction; Suspense fiction